2020
DOI: 10.1101/2020.11.26.399469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CHD8 haploinsufficiency alters the developmental trajectories of human excitatory and inhibitory neurons linking autism phenotypes with transient cellular defects

Abstract: Chromodomain helicase DNA-binding 8 (CHD8) is one of the most frequently mutated genes causative of autism spectrum disorder (ASD). While its phenotypic spectrum often encompasses macrocephaly and hence implicates cortical abnormalities in this form of ASD, the neurodevelopmental impact of human CHD8 haploinsufficiency remains unexplored. Here we combined human cerebral organoids and single cell transcriptomics to define the effect of ASD-linked CHD8 mutations on human cortical development. We found that CHD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
6
6
0
Order By: Relevance
“…While it is tempting to speculate that these findings might apply to individuals with mutations in CHD8 , we are not aware of any study on human brain tissues to support this hypothesis. In this respect, pluripotent stem cell-derived cerebral organoids (see below [ 76 ]) could help to bridge the gap between mice and human studies.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is tempting to speculate that these findings might apply to individuals with mutations in CHD8 , we are not aware of any study on human brain tissues to support this hypothesis. In this respect, pluripotent stem cell-derived cerebral organoids (see below [ 76 ]) could help to bridge the gap between mice and human studies.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Embryonic stem cell (ESC) and induced pluripotent stem cell (iPSC) derived neuronal cell types exhibit genetically encoded molecular and cellular phenotypes matching human mid- to late-term brain development. Most recently, Villa et al [ 76 ] reported the effect of CHD8 mutations on human cortical development by combining the generation of ESC-derived human cerebral organoids with single cell transcriptomics. By adopting an isogenic design of patient-specific mutations, wild-type and mutated CHD8 conditions were investigated on identical genetic backgrounds.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Until recently, the production of cerebral organoids has been labor-intensive and plagued by high organoid-to-organoid variability. Refinements in culturing techniques [ 81 ] and progress toward fully automated high-throughput workflows for human organoid production and analysis [ 87 ] open the perspective to enlarge sample sizes in terms of the number of independent donors and genes to be investigated. Improvements in reproducibility are likewise important to cost reduction and statistical analysis [ 88 ].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In light of the importance of this compartment for human cortical growth, the authors suggested that human brain development might be more vulnerable to CHD8 dosage than the mouse. Strikingly, Villa et al [ 81 ] described in human cerebral organoids a shift in the proliferation/differentiation dynamics of neural progenitors that drove the expansion of this compartment and a subsequent increase in the number of later neurons. At the same time, however, the number of Tbr2-positive intermediate progenitors actually decreased.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation